2005
DOI: 10.1542/peds.2005-0104
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Overweight Among Pediatric Users of Community Health Centers

Abstract: Conclusions. The present study identified a population of children at particularly high risk for obesity based on the type of health care delivery system they use regardless of race/ethnicity or geographic characteristics. Because community health centers are experienced in prevention and serve >4.7 million children in the United States, they may be a particularly promising point of access and setting for pediatric obesity prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Furthermore, Hispanics had the lowest income level, and whites had the highest (not shown). As we expected on the basis of prevalence data from the overall CHC sample (Stettler et al 2005), a high proportion of the children were overweight (23%) or at risk of becoming overweight (14%), which is higher than would be expected for children in this age range in the U.S. population as a whole (Ogden et al 2006 Tables 2 and 3 show responses for parents' reported exposure to fast-food promotions, access to fast-food restaurants, and attitudes and social norms, and Table 4 shows the frequency of children's fast-food consumption. We present data for the total sample and by race/ethnicity.…”
Section: Methodssupporting
confidence: 59%
“…Furthermore, Hispanics had the lowest income level, and whites had the highest (not shown). As we expected on the basis of prevalence data from the overall CHC sample (Stettler et al 2005), a high proportion of the children were overweight (23%) or at risk of becoming overweight (14%), which is higher than would be expected for children in this age range in the U.S. population as a whole (Ogden et al 2006 Tables 2 and 3 show responses for parents' reported exposure to fast-food promotions, access to fast-food restaurants, and attitudes and social norms, and Table 4 shows the frequency of children's fast-food consumption. We present data for the total sample and by race/ethnicity.…”
Section: Methodssupporting
confidence: 59%
“…Although the prevalence of osteoporosis and related fragility fracture is lower in African American women compared with white women, osteoporosis is not uncommon in the African American adult population 70,71 and may be underdiagnosed. 72 Additional study is needed to better understand and improve bone health in the African American population given our study findings of an increased prevalence of factors associated with forearm fracture risk, [24][25][26][27][28][29][30] higher rates of some fractures, 32,33 and the apparent paradox of a relatively increased BMD in comparison with white children. 31 …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] African American children are also more likely than white children to be overweight or obese. [27][28][29] Additionally, darker skin pigmentation is a risk factor for vitamin D deficiency. 30 Although African American children have a relatively increased BMD in comparison with white children and studies of a South African cohort show higher fracture rates in white children, other studies show a higher incidence of femur fracture and fracture-related hospitalizations in African American children.…”
mentioning
confidence: 99%
“…7,8 Obesity has long been associated with low socioeconomic status (SES). 9 Indeed, characteristics of health and healthcare associated with low SES may be true of residents of both rural areas and inner-city urban areas.…”
Section: Introductionmentioning
confidence: 99%